IMPLEMENTASI ACTIVE DIRECTORY PADA JARINGAN KOMPUTER PKMI 1 MEDAN - Fati Gratianus Nafiri Larosa (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Computer Network can optimize using Client/Server model (Domain based). There are a lot of benefits if using that model especially for centralized management and security system. There is (a) Organizational Unit Management, (b) Group Management, (c) Domain User Management, (d) Home Folder Management, (e) Group Policy Management and so on. Users can do anything on their computer even though convenience decreases to make system more secure. Users do their work individually with high attention. The good circumstance achieved because Server using Microsoft Windows Server 2003, one of Operating System support Client/Server model. The feature inside is Active Directory. Client using Microsoft Windows XP and must join to domain. And the users can logon through Client as a domain user, not as local user anymore. Client/Server model should managed by Network Administrator more efficient and effective.